The Impacts of Alexithymia and Sexual Distress on Sexual Functioning Among Portuguese Women - Ribeiro, Celina; Pereira, Henrique (European Journal of Mental Health, 2023)
Introduction: Recognizing own’s emotions seems to have an important role regarding not only our overall well-being, but also our sexual functioning.Aims: The aim of this study is to analyze the association or impact of alexithymia on female sexual functioning.Methods: 459 Portuguese women, with a mean age of 34.57 years (SD = 10.27), ranging from 18 to 65 years, completed the Toronto Alexithymia Scale (TAS-20), the Female Sexual Distress Scale – Revised (FSDS-R) and, additionally, completed the Female Sexual Function Index (FSFI), indicating if and when a sexual relationship occurred in the last month.Results: The results showed that higher levels of alexithymia were associated with worse sexual functioning and higher levels of sexual distress. Higher levels of sexual distress were associated with worse sexual functioning. It was possible to establish a significant linear regression model between dimensions of alexithymia (difficulties in identifying feelings and difficulties in describing feelings) and sexual distress in sexual functioning; the variables together explained about 45.2% of sexual functioning in these women.Conclusions: The results emphasize the relevance of alexithymia’s dimensions in sexual functioning concerning women with or without sexual dysfunction, since they present themselves as significant predictors. Professionals working in women's sexual health should take this into account for more effective assessment and intervention in matters concerning sexual health.